The role of Intermediate Entities in the governance of regional health systems: From the analysis of emerging structures to the case of Calabria - Rotundo, Giorgia; Giancotti, Monica; Profiti, Giuseppe; Reali, Luca; Mauro, Marianna (Mecosan - Management ed Economia Sanitaria - Open Access, 2025)
Following the institutional and governance structure changes of the 1990s reforms, Italian regional health systems have undergone a re-centralization process which leads to the creation of Intermediate Entities located among the Region and health structures. The study aims to provide an overview of the functions attributed to the Intermediate Entities, focusing on the Calabria Region, the last in the establishment. The analysis of the functions performed provides the first observations about the points of convergence and divergence among the emerging institutional structures. Regarding the Calabrian case, apart from the considerable advantages, the critical issues related to the establishment of the new Entity are not negligible, both relating to the internal regional order and to the future operational phase.